Interstitial boron-doped mesoporous semiconductor oxides for ultratransparent energy storage - Jian Zhi (Nature Portfolio, 2021)
Realizing transparent supercapacitor is hindered by the trade-off between capacitance and transparency of the electrode material. Here, the authors report an interstitial doping strategy to boost the electrochemical activity of transparent conducting oxides while maintaining their optical feature.